(untitled) - Evers, Hans-Dieter (Bonn, 2009)
This project analyses how research is organised and trace the foundation of knowledgeproducing institutions since the reunification of Vietnam. Based on the field research data authors map and analyse the building of knowledge clusters and, finally, evaluate the impact of cluster formation on knowledge production. Given the importance of the water sector in the Mekong Delta. The authors also emphasise the importance of knowledge sharing and networking and discuss the hypothesis that a lack of knowledge sharing diminishes the positive impact of knowledge clusters on social and economic development.
Keywords: Dams,Đê đập; Design and construction,Thiết kế và xây dựng